2014
DOI: 10.1115/1.4028020
|View full text |Cite
|
Sign up to set email alerts
|

The Experimental Studies of Improving the Aerodynamic Performance of a Turbine Exhaust System

Abstract: Analysis and testing were conducted to optimize an axial diffuser-collector gas turbine exhaust. Two subsonic wind tunnel facilities were designed and built to support this pro gram. A 1112th scale test rig enabled rapid and efficient evaluation of multiple geome tries. This test facility was designed to run continuously at an inlet Mach number of 0.41 and an inlet hydraulic diameter-based Reynolds number of 3.4 x 10s. A H4th geometric scale test rig was designed and built to validate the data in the 1112th sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 17 publications
(21 reference statements)
0
3
0
Order By: Relevance
“…The validation of the newly-designed diffuser in the test engine has shown that the described design process leads to a noticeable performance improvement and provides quite reliable results. Guillot et al's 42 experimental studies indicated that the design modifications result in a substantial increase in the overall pressure recovery coefficient of 0.07 above the baseline. Furthermore, the numerical investigation of the impact of flow deflection at the upper volute by Munyoki et al 43 showed that, deflector configurations investigated are found to re-direct the flow at the upper volute and to minimize the intensity of the swirling flows hence leading to aerodynamic performance improvement of exhaust volutes.…”
Section: Design Optimization Of Exhaust Volutes Towards Improving the Turbine-volute Performancementioning
confidence: 99%
“…The validation of the newly-designed diffuser in the test engine has shown that the described design process leads to a noticeable performance improvement and provides quite reliable results. Guillot et al's 42 experimental studies indicated that the design modifications result in a substantial increase in the overall pressure recovery coefficient of 0.07 above the baseline. Furthermore, the numerical investigation of the impact of flow deflection at the upper volute by Munyoki et al 43 showed that, deflector configurations investigated are found to re-direct the flow at the upper volute and to minimize the intensity of the swirling flows hence leading to aerodynamic performance improvement of exhaust volutes.…”
Section: Design Optimization Of Exhaust Volutes Towards Improving the Turbine-volute Performancementioning
confidence: 99%
“…Schaefer et al 28 developed the multi-objective aerodynamic optimization of the duct and struts for maximization of the static pressure recovery performance of the exhaust diffuser at two inlet flow conditions. Guillot et al, 29 Xue et al 30 and Siorek et al 31 systematically investigated the flow field and aerodynamic performance of the diffuser-collector exhaust system for industrial gas turbines by experimental measurements and numerical simulations. The redesigned diffuser profile resulted in a substantial increase in the overall pressure recovery coefficient compared with the baseline geometry.…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al 16 presented an aerodynamically optimized design of exhaust volute diffuser for steam turbine combined with three-dimensional parameterization method of exhaust diffuser profile, aerodynamic performance evaluation method, response surface approximation evaluation model, and Hooke-Jeeves direct search approach. Guillot et al 17 conducted the analysis and multiscale testing to optimize the turbine exhaust system. It was observed that the flow features are qualitatively consistent across the scales, although some quantitative differences exist due to Reynolds number effects.…”
Section: Introductionmentioning
confidence: 99%